Crops for ilicit use and peasant transformation processes in La Macarena (Meta, Colombia) - Guerrero, Demis; Acevedo, Álvaro (Agrociencia Uruguay, 2022)
This work addresses the peasant economy as a subject of transformation processes in function of the market. The objective was to determine the relationship between the productive systems and the peasant transformations in the configuration of alternative development plans (PDA) in La Macarena. A mixed methodology was used, combining a systemic methodology with a dialectic one, finding that the peasant resorted to illicit crops immersed in the subject-structure dialectic conditioned by the unsolved agrarian problem. There are four variables that can be managed by the peasantry in the substitution productive systems, arising from the PDA of the National Program for the Substitution of Crops for Illicit Use (PNIS): Energy Efficiency, Cost-Benefit Ratio, Environmental Risk, and Organization; their indices would improve establishing synergies with the endogenous development plans of the Peasant Reserve Zone of Lozada and Guayabero (ZRC-LG).